2012
DOI: 10.1371/journal.pone.0049620
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Levels in Human Red Blood Cells

Abstract: Amyloid β-peptide (Aβ) is hypothesized to play a key role by oxidatively impairing the capacity of red blood cells (RBCs) to deliver oxygen to the brain. These processes are implicated in the pathogenesis of Alzheimer's disease (AD). Although plasma Aβ has been investigated thoroughly, the presence and distribution of Aβ in human RBCs are still unclear. In this study, we quantitated Aβ40 and Aβ42 in human RBCs with ELISA assays, and provided evidence that significant amounts of Aβ could be detected in RBCs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 36 publications
2
62
0
Order By: Relevance
“…Aβ40 and Aβ42 were detected also in RBCs where their levels were found to be about 8-and 14-times higher than those in plasma, respectively [67]. Exposure of RBCs exposed to Aβ on the luminal surface of cerebral microvessels induces the erythrocytes' adhesion to endothelial cells and affects endothelial functionality [68].…”
Section: Aβ-induced Morphological Changes In Erythrocytesmentioning
confidence: 98%
See 1 more Smart Citation
“…Aβ40 and Aβ42 were detected also in RBCs where their levels were found to be about 8-and 14-times higher than those in plasma, respectively [67]. Exposure of RBCs exposed to Aβ on the luminal surface of cerebral microvessels induces the erythrocytes' adhesion to endothelial cells and affects endothelial functionality [68].…”
Section: Aβ-induced Morphological Changes In Erythrocytesmentioning
confidence: 98%
“…Exposure of RBCs exposed to Aβ on the luminal surface of cerebral microvessels induces the erythrocytes' adhesion to endothelial cells and affects endothelial functionality [68]. In addition, bounding of Aβ to RBCs impairs the capacity of RBCs for delivering oxygen thereby facilitating AD [65][66][67][68][69]. It was shown that oxidative stress and ROS production in RBC membranes was induced particularly by copper-bound Aβ [65].…”
Section: Aβ-induced Morphological Changes In Erythrocytesmentioning
confidence: 99%
“…Together, these studies suggest that Ab plays a key role in the blood and oxidatively impairs the function of RBCs, which is important for adequate O 2 supply to the brain. Kiko et al [120] reported that human RBC-Ab 1-40 and -Ab 1-42 levels increased with aging and imply a pathogenic role for RBC-Ab. RBC membranes in AD patients are injured by unavoidable exposure to Ab [120].…”
Section: Effect Of Dha On Lipid Raftsmentioning
confidence: 99%
“…Kiko et al [120] reported that human RBC-Ab 1-40 and -Ab 1-42 levels increased with aging and imply a pathogenic role for RBC-Ab. RBC membranes in AD patients are injured by unavoidable exposure to Ab [120]. The reasoning is that once amyloid b peptides (Abs) of Alzheimer's disease build in the blood circulation, they are capable of binding RBCs and inducing hemolysis.…”
Section: Effect Of Dha On Lipid Raftsmentioning
confidence: 99%
“…In accord with this hypothesis, we found recently evidence that A is indeed present in human RBCs. 59) Based on these findings, we are currently collecting blood samples from living AD subjects to investigate further the oxidative and pathogenic roles of RBC A and the suitability of RBC A as a biomarker for AD. On the other hand, it is well recognized that one of the major physiological activities of carotenoids is their antioxidant action and their protective effect against lipid peroxidation in biological membranes.…”
Section: Rbc Lipid Peroxidation May Be Involved In the Pathogenesis Omentioning
confidence: 99%